Interrelated responses of tomato plants and the leaf miner Tuta absoluta to nitrogen supply. (26th December 2015) - Larbat, R.; Adamowicz, S.; Robin, C.; Han, P.; Desneux, N.; Le Bot, J.
Abstract: Plant–insect interactions are strongly modified by environmental factors. This study evaluates the influence of nitrogen fertilisation on the tomato ( Solanum lycopersicum L.) cv. Santa clara and the leafminer ( Tuta absoluta (Meyrick), Lepidoptera: Gelechiidae). Greenhouse‐grown tomato plants were fed hydroponically on a complete nutrient solution containing either a high nitrogen concentration (HN) sustaining maximum growth or a low nitrogen concentration (LN) limiting plant growth. Insect‐free plants were compared with plants attacked by T. absoluta . Seven and 14 days after artificial oviposition leading to efficacious hatching and larvae development, we measured total carbon, nitrogen and soluble protein as well as defence compounds (phenolics, glycoalkaloids, polyphenol oxidase activity) in the HN versus LN plants. Only in the HN treatment did T. absoluta infestation slightly impair leaf growth and induce polyphenol oxidase (PPO) activity in the foliage. Neither the concentration of phenolic compounds and proteins nor the distribution of nitrogen within the plant was affected by T. absoluta infestation. In contrast, LN nutrition impaired T. absoluta ‐induced PPO activity. It decreased protein and total nitrogen concentration of plant organs and enhanced the accumulation of constitutive phenolics and tomatine. Moreover, LN nutrition impaired T. absoluta development by notably decreasing pupal weight and lengthening the development period from egg to adult. Adjusting the level of nitrogen nutrition may thus be a means of altering the life cycle of T. absoluta . This study provides a comprehensive dataset concerning interrelated responses of tomato plants and T. absoluta to nitrogen nutrition.